Quantitative evaluation of traditional Chinese medicine development policy: A PMC index model approach - Yang, Ciran; Yin, Shicheng; Cui, Dan; Mao, Zongfu; Sun, Yu; Jia, Changli; An, Shuhan; Wu, Yuxin; Li, Xue; Du, Yixin; Zhao, Qiuling; Wang, Rui; et al. (Frontiers in Public Health, 2022)
Background: Traditional Chinese medicine development policies (TCMDPs) are essential in improving the sustainable development of TCM undertakings, of which transmissions of policy information are closely related to the actual policy effectiveness. However, the inherent components of TCMDPs had not been explored from the structural dimension of policy design. Methods: Based on the policy modeling consistency (PMC) index model, we constructed a comprehensive evaluation system, including ten first-level and 40 second-level indicators, and focused on the TCMDPs released by the Chinese central government in the past 42 years (1980-2022) to conduct multi-dimensional inspections to TCMDPs by analyzing the overall policy quality, individual scoring performance, and indicators distribution characteristics. Results: This study pointed out that four policies were rated as “perfect,” 35 were rated as “superb,” 50 were rated as “excellent,” 28 were rated as “good,” and four were rated as “acceptable,” with total mean values of the PMC index being 7.530±0.835. Although most TCMDPs had appropriate policy structure and consistency, the potential weaknesses in the design of TCMDPs also needed our attention through careful checks on the outlier policy samples. Besides, the existing TCMDPs had room for improvement regarding policy areas, guarantees & incentives, objects included, and issuing agencies. Conclusions: We emphasized that the policy evaluation method used in this current study, the PMC index model, is scarce in the TCMDPs. These findings are helpful for fully understanding the strengths and weaknesses of TCMDPs and provide theoretical references for further studies optimizing TCMDPs.